Calculating Utilities From the Spine Oncology Study Group Outcomes Questionnaire: A Necessity for Economic and Decision Analysis. Issue 17 (1st September 2021) - Pahuta, Markian A.; Fisk, Felicity; Versteeg, Anne L.; Fisher, Charles G.; Sahgal, Arjun; Gokaslan, Ziya L.; Reynolds, Jeremy J.; Laufer, Ilya; Lazary, Aron; Rhines, Laurence D.; Boriani, Stefano; Bettegowda, Chetan; et al.
Abstract : Study Design: General population utility valuation study. Objective: The aim of this study was to develop a technique for calculating utilities from the Spine Oncology Study Group Outcomes Questionnaire v2.0 (SOSGOQ2.0). Summary of Background Data: The ability to calculate quality-adjusted life-years (QALYs) for metastatic spine disease would enhance treatment decision-making and facilitate economic analysis. QALYs are calculated using utilities. Methods: Using a hybrid concept-retention and factorial analysis shortening approach, we first shortened the SOSGOQ2.0 to eight items (SOSGOQ-8D). This was done to lessen the cognitive burden of the utility valuation exercise. A general population sample of 2730 adults was then asked to evaluate 12 choice sets based on SOSGOQ-8D health states in a Discrete Choice Experiment. A utility scoring rubric was then developed using a mixed multinomial-logit regression model. Results: We were able to reduce the SOSGOQ2.0 to an SOSGOQ-8D with a mean error of 0.003 and mean absolute error of 3.078 compared to the full questionnaire. The regression model demonstrated good predictive performance and was used to develop a utility scoring rubric. Regression results revealed that participants did not regard all SOSGOQ-8D items as equally important. Conclusion: We provide a simple technique for converting the SOSGOQ2.0 to utilities. The ability to evaluate QALYs in metastatic spine disease will facilitate economic analysis and patient counseling. We also quantify the importance of individual SOSGOQ-8D items. Clinicians should heed these findings and offer treatments that maximize function in the most important items. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textQuality-adjusted-life-year weights (utilities) for metastatic disease were measured for the Spine Oncology Study Group Outcomes Questionnaire. Analysis revealed that participants did not regard all questionnaire items as equally important. We provide a simple technique for converting the SOSGOQ2.0 to utilities which will facilitate economic analysis and patient counseling.